1993
DOI: 10.1179/bjo.20.3.215
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Response of Palatally Displaced Canines to the Removal of Deciduous Canines and an Assessment of Factors Contributing to Favourable Eruption

Abstract: The effect of the removal of deciduous canines on palatally displaced maxillary canines was assessed and factors contributing to a successful outcome were analysed. Thirty-nine consecutive patients of mean age 11·2 years (standard deviation 1·43), with 47 palatalfy displaced canines were included in the study. The cases were examined clinically and radiographically for a maximum period of 2 years following deciduous canine removal. Twenty-nine (62 per cent) of the 47 ectopic canines achieved a normal eruptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
2
31

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(201 citation statements)
references
References 8 publications
5
163
2
31
Order By: Relevance
“…Ectopic eruption of canines is reported to be responsible for some 12 per cent of root resorption of permanent incisors in children 10-13 years of age. 9 7. There was also the remote possibility that the teeth may be congenitally missing, or their eruption impeded by some unusual oral pathosis, such as a supernumerary tooth or an odontome.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic eruption of canines is reported to be responsible for some 12 per cent of root resorption of permanent incisors in children 10-13 years of age. 9 7. There was also the remote possibility that the teeth may be congenitally missing, or their eruption impeded by some unusual oral pathosis, such as a supernumerary tooth or an odontome.…”
Section: Discussionmentioning
confidence: 99%
“…A later investigation appeared to confirm this finding, although the success rate was found to be slightly lower (62%). 21 Subsequently, in a longitudinal prospective study of this interceptive technique, 22 it was found that successful permanent canine eruption occurred in 36% of cases in the untreated control group but 65.2% of cases that had had isolated extraction of the deciduous canine, which was statistically significant. Interestingly, when (cervical pull) headgear was used, along with extraction of the deciduous canine, the success rate increased to 87.5%.…”
Section: Interceptive Treatment By Extraction Of the Deciduous Caninementioning
confidence: 97%
“…15 Another preventive measure suggested is the surgical exposure of the superficial and buccally impacted canine which may be enough to induce eruption. 16,17 Clinicians must be vigilant in detection and alerting dental factors include agenesis, dental malformation, short roots, taurodontism, invaginations and abnormal eruption.…”
Section: Aetiologymentioning
confidence: 99%